2007
DOI: 10.1017/s0007114507337306
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the level of iodine in the diet of pregnant ewes on the concentration of immunoglobulin G in the plasma of neonatal lambs following the consumption of colostrum

Abstract: Excessive I in the diet of pregnant sheep can reduce the concentration of antibodies in the blood plasma of the lambs after they have consumed colostrum. Our aim was to determine the dose of dietary I that would avoid this effect, and to relate this to changes in the concentrations of hormones and metabolites in the lambs. Four groups of pregnant ewes received concentrate containing 5·5, 9·9, 14·8, and 21·0 mg I/kg DM, respectively. Hay and molasses (containing 0·16 and 0·29 mg I/kg DM, respectively) were avai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
24
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 17 publications
5
24
1
Order By: Relevance
“…The results of the current study also suggest a positive relationship between T 3 levels in lamb serum and IgG absorption from colostrum as the progeny with the lower T 3 levels had lower IgG absorption efficiency. However, this is not in agreement with the report of Rose et al (2007) where high-level iodine supplementation of the pregnant ewe increased plasma T 4 levels at birth but plasma T 3 levels were unaffected. The exact mechanism through which iodine reduces IgG and vitamin E uptake from colostrum is still unclear.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The results of the current study also suggest a positive relationship between T 3 levels in lamb serum and IgG absorption from colostrum as the progeny with the lower T 3 levels had lower IgG absorption efficiency. However, this is not in agreement with the report of Rose et al (2007) where high-level iodine supplementation of the pregnant ewe increased plasma T 4 levels at birth but plasma T 3 levels were unaffected. The exact mechanism through which iodine reduces IgG and vitamin E uptake from colostrum is still unclear.…”
Section: Discussioncontrasting
confidence: 99%
“…Iodine has been identified as the specific element responsible for this reduced efficiency of IgG absorption from colostrum. Furthermore, iodine supplementation of the pregnant ewe reduced IgG absorption from a colostrum supplement where lambs had no access to maternal colostrum during the first 24 h of life (Rose et al, 2007). Minerals other than iodine have also demonstrated a role in altering lamb serum IgG levels following pre partum maternal supplementation.…”
Section: Introductionmentioning
confidence: 99%
“…In specific livestock species, low immunoglobulin levels in the newborn have been associated with impaired health in later life, thus emphasising the importance of colostrum for the growth and well-being of the newborn (Speikermann et al, 2002). Previous studies have, however, recently demonstrated a negative relationship between iodine supplementation of the pregnant ewe in late gestation and the serum IgG concentration of her progeny at 24 h postpartum (Boland et al, 2006 and2008;Rose et al, 2007).…”
Section: Discussionmentioning
confidence: 94%
“…However, the foetal production of thyroid hormones remains dependent upon iodide uptake from maternal circulation by the follicular cells of the foetal thyroid gland (Choksi et al, 2003). While T 4 is the most predominant thyroid hormone in circulation (Piosik et al, 1997), with concentrations increasing in the lamb before parturition and declining rapidly within the first few days of life (Forhead and Fowden, 2014), T 3 is deemed the most biologically active (Choksi et al, 2003;Rose et al, 2007). There is a strong relationship between both total the free thyroid hormone fractions with circulating levels of T 3 arising from the de-iodination of T 4 by a selenium containing enzyme, type 1 iodothyronine 5'-deiodinase (Barry et al, 1983;Camacho et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation